(untitled) (Journal of the Bangladesh Agricultural University, 2014)
This study was carried out for the isolation and identification of Avibacterium paragallinarum, the etiological agent of infectious coryza (IC). Pathological changes were also investigated that occurred in organs in layer chickens obtained from some selected areas of Bangladesh. A nasal swabs (n=30) from dead chickens and four swabs from live chickens were collected aseptically. The organisms from swabs were cultured in different media, stained, and followed by sugar fermentation and biochemical tests for identification of causal agent. Histopathology of the affected tissues was also carried out. Swabs from nasal passage (n=30) of dead birds died of other diseases cultured but no A. paragallinarum was isolated and identified. Two out of four suspected clinical cases of IC was confirmed by isolation of A. paragallinarum. The clinical signs of all four cases were nasal discharge; conjunctivitis with swelling of the sinuses, face and wattles; decreased feed and water intake with reduced egg production. At necropsy, hemorrhages were in mucous membrane of nasal passage and trachea. Histopathology of the nasal septum showed acanthosis, congestion, mucous glandular cell hyperplasia, hyperplasia of nasal sinus and parakeratosis. Further studies involving serological and molecular identification of the etiological agent of IC are warranted. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18218 J. Bangladesh Agril. Univ. 11(1): 87-96, 2013